HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU SEKSUAL REMAJA DI SMK TEKNOLOGI MIGAS PEKANBARU - Lora Marlita; Putri Wulandini; Erika Siswaty Zega; Yusmaharani Y (LPPM Universitas Abdurrab, 2019)
RELATIONSHIP OF ASUH PARENT PATTERNS WITH SEXUAL BEHAVIOR IN ADOLESCENT IN SMK TECNOLOGY OIL AND GAS MIGAS PEKANBARU TAHUN 2018 Lora Marlita,Yusmaharni,Putri Wulandini S, Erika Siswaty Zega Program Studi D III Keperawatan ABSTRACT Sexual behavior is something that is considered to affect the behavior of self-esteem, parent-child relationships, the tendency to seek sexual sensation, the existence of a deviant peer, and the use of pornographic media. Sexual behavior also occurs, because of the physical changes that occur because of the active sex hormones in the body of a very large influence in the cause of sexual urges. Pattern of parenting is the pattern of interaction between the child and the parents include the fulfillment of physical needs ,and socialization of prevailing norms in the community so that children can live in harmony with their environment. The general purpose of Scientific Writing is To know how the relationship of parental parenting with sexual behavior in adolescents in SMK Tecnology Oil And Gas Pekanbaru, descriptive correlation research design. The research was conducted on June, 2018, the sample in this study were the students in SMK Tecnology Oil And Gas Pekanbaru amounted to 112 people. Research technique area (cluster) sampling. Chi-Square statistical test results obtained p value = 0.204> 0.05, it can be concluded there is no relationship Parenting Parenting With Sexual Behavior In Teenagers In SMK Tecnology Oil And Gas Pekanbaru 2018. Teenagers in SMK Tecnology Oil And Gas Pekanbaru, is expected to direct the association in a positive direction so that the tendency to engage in sexual behavior can be avoided such as following extracurricular activities, religious activities, youth, etc. in accordance with the interests of student talent. Keywords : Patterns of Custody, Sexual Behavior References : 21 references (2007-2017)